Clinical, epidemiological, and molecular aspects of picornaviruses (entero, parecho) in acute gastroenteritis: A study from Pune (Maharashtra), Western India. Issue 6 (14th October 2020) - Gopalkrishna, Varanasi; Ganorkar, Nital; Patil, Pooja; Hedda, Gokul; Ranshing, Sujata; Kulkarni, Ruta
Abstract: Among enteric viruses, rotavirus A (RVA), norovirus (NoV), adenovirus, and astrovirus (AstV) are the major etiological agents associated in acute gastroenteritis. The present study highlights, clinical, epidemiological, and molecular aspects with respect to RVA, NoV, enterovirus (EV), and human parechovirus (HPeVs) in sporadic cases ( n = 305) of acute gastroenteritis, Pune (Maharashtra), Western India. Detection of RVA was carried out by enzyme‐linked immunosorbent assay, NoV, EV, and HPeVs by reverse transcription PCR. Prevalence of 36.06%, 20.32%, 14.09%, 3.93%, respectively was observed for RVA, EV, HPeVs, and NoV along with coinfections. Infections occurred in children less than 2 years old, with peak infections within 12 months age. The disease severity in RV infections was found high (70.90%) with severe disease, followed by EV (62.9%), NoV (58.33%), and HPeV (44.58%). Predominant strains of RV G1P[8], G2P[4] types with unusual G9P[4], NoV Genogroup II of genotype 4 strains and multiple EV types with EV‐B species, E14 and E17 and two novel EV‐75, EV‐107 types were detected. Circulation of heterogeneous HPeV genotypes (HPeV1–5, 7, 8, 13, 14, 16) with predominance of HPeV‐1 was noticed. Changing trends in circulation of a rare HPeV‐2 genotype, with emerging and reemerging strains was noted. The study highlights association of RVA, NoV, EV, and HPeV and their mono‐infections, genotype distribution, and changing trends in acute gastroenteritis, and added more knowledge on rota and nonrota enteric viruses in acute gastroenteritis. More such studies in rota vaccinated era are required across the country, as Indian rotavirus vaccine has been implemented under the National Immunization program.